1987
DOI: 10.1177/07399863870093006
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption Patterns in Immigrant and Later Generation Mexican American Women

Abstract: Using data from a re-analysis of a 1976 survey of alcohol patterns among Latinos in California as a basis of comparison this article summarizes what is known about the drinking practices of immigrant Mexican women. Immigrant Mexican women's alcohol-related practices are compared with those of women in several pertinent groups: Mexicans in Mexico, other U.S. Latinas and, most particularly, later generation Mexican American women. Immigrant women s drinking is also contrasted with that of their male counterparts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 21 publications
5
58
0
Order By: Relevance
“…Higher levels of acculturation have been previously linked to use of alcohol (Caetano 1987;Gilbert 1987;Neff et al 1987), cigarettes (Love et al 2006), marijuana (Amaro et al 1990;Love et al 2006;Miller et al 2008b), cocaine (Amaro et al 1990;Miller et al 2008b), and hard drugs such as PCP, heroin, LSD, barbiturates, and amphetamines (Felix-Ortiz and Newcomb 1992). Other research, however, has suggested that any perceived link is somewhat spurious and that acculturation actually impacts drug use through socialization and psychological factors (Barrett et al 1991).…”
Section: Acculturation and Hispanic Drug Usementioning
confidence: 91%
See 1 more Smart Citation
“…Higher levels of acculturation have been previously linked to use of alcohol (Caetano 1987;Gilbert 1987;Neff et al 1987), cigarettes (Love et al 2006), marijuana (Amaro et al 1990;Love et al 2006;Miller et al 2008b), cocaine (Amaro et al 1990;Miller et al 2008b), and hard drugs such as PCP, heroin, LSD, barbiturates, and amphetamines (Felix-Ortiz and Newcomb 1992). Other research, however, has suggested that any perceived link is somewhat spurious and that acculturation actually impacts drug use through socialization and psychological factors (Barrett et al 1991).…”
Section: Acculturation and Hispanic Drug Usementioning
confidence: 91%
“…Though reliable data on adolescent Hispanic substance use has proved elusive due to the issues discussed above, acculturation has remained a salient factor in most studies of the phenomenon (Neff et al 1987;Caetano 1987;Gilbert 1987;Amaro et al 1990;Love et al 2006;Miller et al 2008b). The traditional view of the acculturative process suggests that as individuals become more assimilated they begin to adopt customs and behaviors common to the new culture.…”
Section: Acculturation and Hispanic Drug Usementioning
confidence: 95%
“…Adverse effects of acculturation have also been reported among Mexican Americans with respect to alcohol consumption patterns (Gilbert, 1989) and psychological distress (Kaplan and Marks, 1990). Indeed, intriguing questions have been raised by recent research on the mental health of ethnic minorities in the United States, including immigrants and refugees.…”
Section: Assimilation and Its Discontentsmentioning
confidence: 99%
“…13,14,20,21 In summary, these data suggest that single female heads of household drink significantly more than women in coupleheaded families. This research indicates that single female heads of household are at increased risk for greater consumption of alcohol.…”
Section: Discussionmentioning
confidence: 90%